Using digital technologies with immigrant plurilingual language learners: A research synthesis - Bangou, Francis; Smith, Cameron W.; Savard, Cindy; Koziol, Heather; Arnott, Stephanie; Fleming, Douglas; Fleuret, Carole; Thibeault, Joël (Cahiers de l’ILOB / OLBI Journal)

(untitled) (Centre canadien d’études et de recherche en bilinguisme et aménagement linguistique (CCERBAL), 2025)
With massive migratory flows observed around the world, schools are experiencing an unprecedented increase in the enrolment of children who speak multiple languages. Educators are called upon to facilitate immigrant plurilingual students’ inclusion and development of functional competencies in the target language(s), often using digital technologies (DTs) to promote language learning and plurilingual teaching practices. This research synthesis explores the research trends, methods, and findings from studies focused on the use of DTs with immigrant plurilingual language learners. The results highlight that DTs are used in heterogeneous contexts to support the development of immigrant plurilingual students’ overall language proficiency, (multi)literacies, engagement, as well as identity development. However, teachers and learners may require additional support to use DTs and plurilingual practices to their full potential. These concerns point to the need for ongoing professional learning and contextualised supports for educators at the intersection of these areas.